Evaluating the Efficacy of the Waste Bank Centre in Kabupaten Kulon Progo: A Comprehensive Study on Sustainable Waste Management Practices - Iva Yenis Septiariva; I Wayan Koko Suryawan (Journal of Sustainable Infrastructure, 2023)
Amidst escalating global concerns regarding waste management, Kabupaten Kulon Progo in Yogyakarta presents a microcosm of the challenges and solutions inherent to Indonesia. This research primarily aims to elucidate the efficacy and impact of the waste bank centre, a pivotal initiative in the district promoting waste reduction, recycling, and proper disposal. Utilizing empirical data from the National Waste Management Information System (SIPSN) and an extensive literature review, the study offers insights into waste trends, composition, and disposal mechanisms specific to Kabupaten Kulon Progo. Further, the research underscores the waste bank center's operational efficiency, outreach, and influence within the broader waste management framework. By highlighting both the challenges and opportunities faced by the waste bank centre, this study crafts informed policy recommendations, aiming to fortify waste management efforts in Kabupaten Kulon Progo and presenting scalable lessons for other Indonesian districts.